Clinical spectrum of hypocalcaemia in children - Ramdasi, Aboli V.; Wade, Minal; Inamdar, Nusrat R. (International Journal of Research in Medical Sciences, 2024)
Background: Hypocalcaemia is a biochemical abnormality commonly seen in paediatric population with a multi-factorial etiology having varied presentation ranging from acute emergency to chronic diagnostic dilemma. We studied the clinical profile of infants and children presenting with hypocalcaemia from 0 to 12 years of age. Methods: Clinical features, risk factors, precipitating factors, feeding/dietary practices of all children (0-12 years) visiting our tertiary care centre, from January 2019 to March 2020, diagnosed with hypocalcaemia were recorded and a correlation with serum calcium levels was studied. Results: Out of 92 patients having hypocalcaemia majority 57 (62%) were males. Majority of participants belonged to age group of 6 months-2 years i.e. 40 (43.48%). The commonest presentation was convulsions present in 39 (42.39%) participants affecting more children less than 2 years of age; whereas majority of children above 2 years of age presented with growth impairment. Risk factors identified were perinatal risk factors, faulty feeding practices in infants, inadequate dietary calcium intake in children, inadequate sun exposure. Amongst the biochemical factors precipitating hypocalcaemia, alkalosis showed significant association (p value 0.016) with degree of hypocalcaemia; most common etiology was vitamin D deficiency and nutritional rickets. Conclusions: Hypocalcemia plays vital role in infants and growing children because of its various implications on growth and development. Exposure to sunlight, vitamin D and calcium supplementation during pregnancy and lactation and infancy with good dietary calcium intake for children during their growth spurts can prevent complications. Health education and awareness of common risk factors for hypocalcaemia can prove helpful.